Análise integrada da paisagem do geocomplexo alto sertão sergipano - Santos, Riclaudio Silva (2018)
The territory of High Backlands of Sergipe comprises the municipalities included in the Development Plan for the Productive Arrangement of Livestock of Milk and Derivatives – High Backlands, of the State Nucleus of Local Productive Arrangements (APL-SE). Considering that all the municipalities of this territory have in common with the milk production, and taking into account that this production presents continuous growth in the last years, this work seeks to understand, through the GTP system, how this average activity the society-nature relationship and the anthropogenic derivations provoked in the environment. The text presents reflections on the characteristic elements that compose the Brazilian semi-arid, as well as the application of systemic thinking in Geography, using remote sensing and geoprocessing to collect data on the different environmental components (geology, geomorphology, pedology, vegetation, atmospheric precipitation), seeking the integrated analysis of the geographic space, using the concepts of Geosystem, Territory and Landscape. To understand the space-time configuration of the anthropogenic flows and derivations of this part of the Backlands of Sergipe, the influence of climatic conditions, and how a milk task present in the milkmaid basin of the state of Sergipe relates to the environmental components.